The invention performance implications of coopetition: How technological, geographical, and product market overlaps shape learning and competitive tension in R&D alliances - Runge, Steffen; Schwens, Christian; Schulz, Matthias (Strategic Management Journal, 2022)
Abstract Research Summary We examine how technological, geographical, and product market overlaps between a firm and its alliance partner influence the firm's invention performance by shaping the learning and competitive tension in an R&D alliance. Drawing on research on learning in alliances and competitive dynamics, we argue that the firm's invention performance is influenced positively by technological and geographical overlaps and negatively by product market overlap. We further argue that product market overlap negatively moderates the positive relationships between technological and geographical overlaps and the firm's invention performance. Testing our theory on a dataset of 215 R&D alliances provides support for most of our hypotheses. We discuss how our theory and findings enrich coopetition and alliance research. Managerial Summary Prominent R&D alliances, such as between BioNtech and Pfizer or Samsung and Sony, typify coopetition—the collaboration between competing firms. In this context of coopetition, we study how a firm's invention performance is influenced by the technological, geographical, and product market overlaps it has with its R&D alliance partner. Empirical results from a sample of 215 R&D alliances formed between U.S. pharmaceutical firms confirm our theory that product market overlap is distinct from the other types of overlap: it changes the thrust of the alliance from joint value creation toward private value appropriation. This way, product market overlap not only decreases a firm's invention performance, but also weakens the positive impacts of technological and geographical overlaps on a firm's invention performance.